2018
DOI: 10.14720/aas.2018.111.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of toxicity on the basis of total phenolic content in oleander leaves (Nerium oleander L.) against Myzus persicae (Sulzer, 1776) (Hemiptera: Aphididae)

Abstract: <p><em></em><em>Nerium oleander</em> is an evergreen flowering shrub or small tree distributed widely in the Mediterranean region. It is also a source of polyphenols and cardenolides ?? with insecticidal effect which could be a safe alternative of chemical control of insect pests. In the present work, five concentrations (0 %, 1 %, 2.5 %, 5 %, and 10 %) of ethanolic extract from <em>Nerium oleander </em>leaves<em> </em>were evaluated for its insecticidal ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Yadav and Patel (2018) There are also many different studies associated with the effectiveness of extracts from different plants against these pest species. For instance, Czerniewicz et al (2018) tested the toxic effects of plant essential oils obtained from Santolina chamaecyparissus, Achillea millefolium, Tanacetum vulgare, Tagetes patula, and Artemisia absinthium on M. persicae and found LC 50 values of 0.34%, 0.34%, 0.47%, 0.61% and 0.69%, respectively, after 24 h. The ethanol extract of Nerium oleander with a 10% concentration showed 70% mortality on M. persicae nymphs (Nia et al, 2018). Mohmed (2019) indicated that Carissa macrocarpa extract, caused the toxic effect at 46.6% on A. fabae.…”
Section: Dose Mortality Resultsmentioning
confidence: 99%
“…Yadav and Patel (2018) There are also many different studies associated with the effectiveness of extracts from different plants against these pest species. For instance, Czerniewicz et al (2018) tested the toxic effects of plant essential oils obtained from Santolina chamaecyparissus, Achillea millefolium, Tanacetum vulgare, Tagetes patula, and Artemisia absinthium on M. persicae and found LC 50 values of 0.34%, 0.34%, 0.47%, 0.61% and 0.69%, respectively, after 24 h. The ethanol extract of Nerium oleander with a 10% concentration showed 70% mortality on M. persicae nymphs (Nia et al, 2018). Mohmed (2019) indicated that Carissa macrocarpa extract, caused the toxic effect at 46.6% on A. fabae.…”
Section: Dose Mortality Resultsmentioning
confidence: 99%